Sleeping Schedule-Aware Local Broadcast in Wireless Sensor Networks. (18th December 2013) - Hong, Jue; Li, Zhuo; Lu, Dianjie; Lu, Sanglu
Abstract : Broadcast is widely used in applications in wireless sensor networks (WSNs). In the last decade, the broadcast problem in WSNs has been well studied. However, few of existing broadcasting strategies have considered the scenarios with sleeping schedules, which have been emerging as a prevalent energy-saving method for WSNs. In WSNs with sleeping schedule, each node switches on and off periodically, rendering the broadcast problem more difficult. To handle the periodical sleep issue, we focus on designing effective sleeping schedule-aware broadcast algorithms. We practically propose SALB, a sleeping schedule-aware local broadcast algorithm. In SALB, a typical local algorithm for constructing connected dominating set is employed to form the broadcast backbone. To guarantee proper transmission of broadcast messages, a sleep-aware forwarding mechanism is implemented. Moreover, heuristic strategies are used to decrease the number of transmissions and the broadcast latency. Theoretical analysis shows that the number of transmissions for SALB is within 4(min(Δ, | T | ) + c ) (c is constant) is constant) times of the optimal value. And the broadcast latency of SALB is within 4| T | + 1 times of the optimal value (Δ is the maximum degree in the network, | T | is the scheduling period length). The performance of SALB is evaluated via simulations.